Transformasi Pedagogis dalam Learning Management System: Integrasi Model Pembelajaran Kontemporer, Adaptivitas, dan Pengembangan Kompetensi Abad 21 - Gunawan Gunawan; Hairunnisyah Sahidu; Lovy Herayanti (Indonesian Publication Center, 2021)
This narrative review examines the pedagogical transformation of Learning Management Systems (LMS) in higher education, shifting from static administrative utilities to dynamic instructional ecosystems. Synthesizing 20 scholarly articles published between 2011 and 2020, this study explores the integration of contemporary learning models, intelligent adaptivity, and 21st-century competency cultivation. The findings reveal that effective LMS optimization relies on three interconnected pillars: the embedding of student-centered frameworks (constructivism, scientific approach, PBL, and STEAM); the engineering of intelligent, personalized learning pathways based on heterogeneous learner profiles; and the intentional stimulation of higher-order thinking skills, particularly creativity, collaboration, and scientific argumentation. Additionally, successful digital adoption is fundamentally governed by user-centered design principles and educators' socio-cultural readiness to navigate systemic flexibility. Ultimately, balancing formal institutional regulations with learner autonomy through intelligent LMS architecture is paramount for ensuring sustainable, high-quality digital higher education.